2015
DOI: 10.1186/s12958-015-0015-2
|View full text |Cite
|
Sign up to set email alerts
|

Isoform 165 of vascular endothelial growth factor in collagen matrix improves ovine cryopreserved ovarian tissue revascularisation after xenotransplantation in mice

Abstract: BackgroundAggressive anti-cancer treatments can result in ovarian failure. Ovarian cryopreservation has been developed to preserve the fertility of young women, but early graft revascularisation still requires improvement.MethodsFrozen/thawed sheep ovarian cortical biopsies were embedded in collagen matrix with or without isoform 165 of vascular endothelial growth factor (VEGF165) and transplanted into ovaries of immunodeficient mice. Ovaries were chosen as transplantation sites to more closely resemble clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 51 publications
2
37
0
1
Order By: Relevance
“…Administration of VEGF, either by culture of the tissue before transplantation or by hydrogel delivery, promoted angiogenesis, follicular survival and enhanced the function of ovarian tissue xenotransplants, including human (Shikanov et al, 2011;Labied et al, 2013;Wang et al, 2013;Henry et al, 2015;Langbeen et al, 2016;Tavana et al, 2016). A previous study on autotransplantation of mouse ITT revealed a positive short-term effect of VEGF on transplant neovascularization 5 and 21 days post-transplantation (Poels et al, 2016), whereas the enhancement of germ cell survival has been demonstrated in several species, including mouse, pig and bovine (Schmidt et al, 2006;Caires et al, 2009Caires et al, , 2012Dores and Dobrinsky, 2014;Poels et al, 2016, Tian et al, 2016.…”
Section: Introductionmentioning
confidence: 99%
“…Administration of VEGF, either by culture of the tissue before transplantation or by hydrogel delivery, promoted angiogenesis, follicular survival and enhanced the function of ovarian tissue xenotransplants, including human (Shikanov et al, 2011;Labied et al, 2013;Wang et al, 2013;Henry et al, 2015;Langbeen et al, 2016;Tavana et al, 2016). A previous study on autotransplantation of mouse ITT revealed a positive short-term effect of VEGF on transplant neovascularization 5 and 21 days post-transplantation (Poels et al, 2016), whereas the enhancement of germ cell survival has been demonstrated in several species, including mouse, pig and bovine (Schmidt et al, 2006;Caires et al, 2009Caires et al, , 2012Dores and Dobrinsky, 2014;Poels et al, 2016, Tian et al, 2016.…”
Section: Introductionmentioning
confidence: 99%
“…In animal models, it has been increasingly common to transplant ovarian tissue installed in acellular scaffolds of materials such as fibrin [11][12][13], alginate [14], Matrigel [15], and collagen [16]. However, there is still no consensus on the ideal material.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in a previous study, granulosa cells, more so than oocytes, were identified as the main cells affected by the freeze/thaw processing of ovarian tissue [13]. Granulosa cells seem to be able to respond to hypoxia by increasing their synthesis of vascular endothelial growth factor (VEGF) [14], which is an important angiogenic factor that could reduce the hypoxic period post-transplantation, as previously shown in ovarian grafting studies [11,[15][16][17][18][19][20]. Because of the restricted availability and relatively short life span of primary cultures of granulosa cells, human granulosa cell lines were developed to facilitate research [21].…”
Section: Introductionmentioning
confidence: 70%